Quantum interference effects at room temperature in OPV-based single-molecule junctions - Arroyo, Carlos R (Springer, 2013)
Interference effects on charge transport through an individual molecule can lead to a notable modulation and suppression on its conductance. In this letter, we report the observation of quantum interference effects occurring at room temperature in single-molecule junctions based on oligo(3)-phenylenevinylene (OPV3) derivatives, in which the central benzene ring is coupled to either para- or meta-positions. Using the break-junction technique, we find that the conductance for a single meta-OPV3 molecule wired between gold electrodes is one order of magnitude smaller than that of a para-OPV3 molecule. Theoretical calculations confirm the occurrence of constructive and destructive interference in the para- and meta-OPV3 molecules respectively, which arises from the phase difference of the transmission coefficients through the molecular orbitals.